Student Learning Independence through Blended Learning Flipped Classroom type during the Covid-19 Pandemic - Puspitasari, Yulia Dewi; Imega Syahlita Dewi (International Journal of Educational Research & Social Sciences, 2021)
This study aims to describe the learning independence of 3rd semester students Academic 2021-2022 through the Flipped Classroom type Blended Learning learning model in the time of the Covid-19 pandemic. This research is a descriptive quantitative research which is analyzed by using a percentage. Data were collected using a questionnaire in the form of statements and scoring using a Likert scale. The results of the study show the percentage of independent learning outcomes from the 6 indicators are: 1) independence from other people gain a percentage of 91,27% with a very good category, 2) have confidence self-acquisition percentage is 90,18% with very good category, 3) behaves in acquisition discipline the percentage is 89,45% with good category, 4) have a sense of responsibility to get the percentage 94,18% with very good category, 5) behave based on own initiative gain percentage 92,36% with very good category, 6) do self-control to gain percentage 92% with very good category. Overall, student learning independence through the Flipped Classroom type Blended Learning learning model obtained a percentage of 91,57% with very good category.